Workshop dan Praktik Wirausaha Muda “Peran Generasi Muda Dalam Menumbuh Kembangkan Jiwa Entrepreneur yang Kreatif, Mandiri, dan Berdaya Saing” - Hengki Mangiring Parulian Simarmata; Pardede, Henry Dunan; Simarmata, Poltak Pardamean; Saragih, Doris Yolanda (Jurnal Pelayanan Masyarakat, 2024)
Young entrepreneurship has become a trend among students with the development of technology and social media today. The aim of this activity is to increase the knowledge and enthusiasm of students in the city of Pematangsiantar so they understand the concept of entrepreneurship and its management strategies. Activity theme: The Role of the Young Generation in Developing a Creative, Independent and Competitive Entrepreneurial Spirit. This activity was attended by 200 students and displayed the results of group product trials. Participants came from invitations from several universities in Pematangsiantar City. The activity was held in collaboration with Murni Teguh PSDKU Pematangsiantar University, the Kelompok Tani Nelayan Andalan (KTNA), Pematangsiantar Tax Office. The results of the activity showed that 90% were satisfied with the material presented and there was an interactive discussion that provided solutions to problems faced by students so far through the distributed Google form